Research on Dynamic Load Sharing Performance of Concentric Face Gear Transmission System Considering Floating Amount - Laiyang Shan; Zhengminqing Li; Hong Zhang (Jixie chuandong)
Based on the lumped mass method， bending and torsion coupled dynamics model of the concentric face gear transmission system is established. The calculation method of floating quantity of input pinion is studied， the system dynamic equation is modified， and the calculation method of dynamic load sharing coefficient is defined. A practical calculation example is given to analyze the influence of input gear floating quantity on system load sharing performance. The results show that the dynamic load sharing performance of the system is affected by the fluctuation of the input pinion， the dynamic load sharing performance of the system is the best when the two input pinions are floating， and the dynamic load sharing performance of the system is the worst when a certain input pinion is floating alone. The load sharing performance test is carried out on the concentric face gear test bench， which verified the reliability of the load sharing performance analysis when the two input gears are floating under a certain supporting structure.